Application of a thermo-sensitive imprinted SERS substrate to the rapid trace detection of ofloxacin. Issue 39 (18th September 2020) - Jiang, Caiyun; Wu, Ting; Liu, Jiaxun; Wang, Yuping
Abstract : The hydrogels combine Raman enhancement of AgNPs, the selectivity of molecularly imprinted materials and the intelligent response of thermo-sensitive hydrogels. Abstract : A novel composite (AgNPs-MIPs) was prepared by combining nano-silver particles with an ofloxacin (OFL) imprinted thermo-sensitive hydrogel. The thermo-sensitive optical properties of the composite were studied and it was used as a Raman substrate for the detection of ofloxacin. The results have shown that the position and intensity of the plasmon resonance absorption peak of the AgNPs-MIPs can be reversibly changed with the change of temperature, and the intensity of the ofloxacin Raman signal increases with the increase of temperature. Because the hydrogel combined Raman enhancement of silver nanoparticles, the selectivity of molecularly imprinted materials and the intelligent response of thermo-sensitive hydrogels, it can realize rapid, in situ, trace and selective detection of ofloxacin. Moreover, the detection limit can reach 10 −10 mol L −1 .